Characterization of Bipolar Vague Soft S -Open Sets - Afzal, F. (Hindawi Limited, 2022)
This paper concerns the study of the concept of bipolar vague soft s-open set, bipolar vague soft s-interior, bipolar vague soft s-closer, and bipolar vague soft s-exterior in bipolar vague soft topological spaces. By using such concepts, some results are addressed in bipolar vague soft topological spaces. The engagements among these results are also addressed by using bipolar vague soft s-open sets. Â© 2022 Farkhanda Afzal et al.